2013
DOI: 10.1167/13.14.9
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous spatial attention: Evidence for intact functioning in adults with autism spectrum disorder

Abstract: Deficits or atypicalities in attention have been reported in individuals with autism spectrum disorder (ASD), yet no consensus on the nature of these deficits has emerged. We conducted three experiments that paired a peripheral precue with a covert discrimination task, using protocols for which the effects of covert exogenous spatial attention on early vision have been well established in typically developing populations. Experiment 1 assessed changes in contrast sensitivity, using orientation discrimination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 47 publications
8
54
1
Order By: Relevance
“…Additional simulations examining how changes in the extent of neuronal pooling and the semisaturation constant affect the model responses are shown in SI Appendix, Fig. S3 D and E. It is further interesting to note that our results may explain the apparent conflict between the study by Robertson et al (45) and another recent study suggesting that exogenous spatial attention may not be affected in autism (46). Specifically, because the attentional field was the same for the control and autism models, the differences in their responses were entirely due to the difference in their suppressive field gain terms.…”
Section: Simulation 2: Tunnel Visionmentioning
confidence: 78%
“…Additional simulations examining how changes in the extent of neuronal pooling and the semisaturation constant affect the model responses are shown in SI Appendix, Fig. S3 D and E. It is further interesting to note that our results may explain the apparent conflict between the study by Robertson et al (45) and another recent study suggesting that exogenous spatial attention may not be affected in autism (46). Specifically, because the attentional field was the same for the control and autism models, the differences in their responses were entirely due to the difference in their suppressive field gain terms.…”
Section: Simulation 2: Tunnel Visionmentioning
confidence: 78%
“…Such an explanation may not apply to all attentional tasks. Grubb et al (2013) have reported that there is no difference in exogenous covert attention, the involuntary allocation of spatial attention to rapid onset cues, when comparing adults with high-functioning ASD and typically developing adults. It is unclear whether the lack of difference between groups that they reported arises from equivalent sensitivity to cuing in the attentional tasks they chose or the choice of the comparison group.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether the lack of difference between groups that they reported arises from equivalent sensitivity to cuing in the attentional tasks they chose or the choice of the comparison group. Our visual search studies have repeatedly shown performance differences using a low AQ comparison group whereas Grubb et al (2013) have used a typically developing group, which is likely to cover a much broader range of the AQ spectrum. Since the visual search differences we obtain are correlated with AQ scores, selection of the comparison group is likely to be important.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these studies used highly controlled psychophysical methods to isolate attention, and found that exogenous and endogenous attention cues robustly modulated visual discriminability to the same extent in both autism and control groups across several different tasks (Grubb et al, 2013a; 2013b). Renner et al (2006) also found no significant difference in endogenous attention, but found impaired exogenous attention in children with autism.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Ciesielski et al (1995) also found no evidence for behavioral differences in focused auditory and visual tasks, or in divided auditory and visual tasks, but did note that attentional modulation of event-related potentials (ERPs) was significantly weaker in individuals with autism. Furthermore, several studies have even reported stronger attentional modulation in autism than controls (Oades et al, 1988), leading to superiority in visual search, which is less affected by the presence of distractors (O'Riordan et al, 2001; Kaldy et al, 2013, Ohta et al, 2012; but see Grubb et al, 2013ba; 2013b). Some have attributed the superior visual search capabilities in autism to attentional, rather than sensory, processes (Happé & Frith, 2006; Kaldy et al, 2013), because visual search performance did not reliably correlate with enhanced perceptual discrimination (Brock et al, 2011).…”
Section: 0 Introductionmentioning
confidence: 99%